2001
DOI: 10.1128/jvi.75.21.10149-10160.2001
|View full text |Cite
|
Sign up to set email alerts
|

The R3 Region, One of Three Major Repetitive Regions of Human Herpesvirus 6, Is a Strong Enhancer of Immediate-Early Gene U95

Abstract: An immediate-early (IE) gene of human herpesvirus 6 (HHV-6), U95, has similarity at the amino acid level to the murine cytomegalovirus (MCMV) IE2 gene and is related to the human cytomegalovirus (HCMV) US22 gene family. Sequence analyses of U95 cDNA clones revealed that the transcription start site was located about 1.6 kbp upstream of the putative initiating ATG and that the transcript consisted of two exons. A single intron extended from nucleotides 142589 to 144229, which contained ORF U94. A protein with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 55 publications
3
36
0
1
Order By: Relevance
“…The seven genes that were expressed independently of de novo protein synthesis (U81, U86, U94, U95, B3, B6, and B7) belonged to the classes I and II, showing the most rapid onset of expression consistent with these genes being IE genes. For three of these genes (U81, U94, and U95), our analysis confirmed their previous classification as IE genes (18,26,36). Furthermore, U86 is homologous to IE-A in HHV-6A (13) and IE2 (UL122) in HCMV, and therefore it is expected to be an IE gene.…”
Section: Discussionsupporting
confidence: 74%
“…The seven genes that were expressed independently of de novo protein synthesis (U81, U86, U94, U95, B3, B6, and B7) belonged to the classes I and II, showing the most rapid onset of expression consistent with these genes being IE genes. For three of these genes (U81, U94, and U95), our analysis confirmed their previous classification as IE genes (18,26,36). Furthermore, U86 is homologous to IE-A in HHV-6A (13) and IE2 (UL122) in HCMV, and therefore it is expected to be an IE gene.…”
Section: Discussionsupporting
confidence: 74%
“…The comparison of kinetic classifications of HHV-6 genes between different studies showed that, despite the use of different methodologies, viral variants and strains, the consistent classification of U90 and U95 as IE genes (Isegawa et al, 1998;Schiewe et al, 1994;Takemoto et al, 2001), of U41, U51 and U69 as E genes Mirandola et al, 1998) and of U22 and U100 as L genes [no detectable transcription in the presence of PAA as reported by French et al (1999) and Mirandola et al (1998)] suggests that these represent ideal markers for determining the stages of HHV-6 lytic replication.…”
Section: Discussionmentioning
confidence: 99%
“…Umbilical cord blood mononuclear cells (CBMCs) were separated on a Ficoll-Conray gradient and cultured in RPMI medium containing 10% fetal bovine serum, phytohemagglutinin (5 g/ml), and interleukin-2 (IL-2) (2 ng/ml) (29). HHV-6A strain U1102 or HHV-6B strain HST was propagated in stimulated CBMCs (1).…”
Section: Cells and Viruses The Human T-lymphoblastoid Cell Lines Jjhmentioning
confidence: 99%